Analysis of the Indonesian Banking System: A Comparison Between Conventional and Sharia Banks - Hafiz, Ahsan Putra; Latif, Mukhtar; Muhammad, Pauzi; Umar, M. Hasbi; Adawiyah, Robi'atul; Husin, Midhat; Sibawaihi, Muhammad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This article discusses the banking system, both conventional and Islamic. Conventional adopts the bank interest system, while Islamic adopts the profit-sharing system. The main findings from the literature indicate that Islamic banks, through the profit-sharing system, offer a more equitable distribution of wealth and are considered to have a better risk-sharing mechanism, especially during periods of financial instability. However, the profit-sharing system often faces challenges related to transparency and monitoring, which can potentially affect operational efficiency. In contrast, conventional banks, although benefiting from a simpler interest-based structure, may expose their customers to interest rate volatility and lack the social justice dimension emphasized in Islamic finance.  [Artikel ini membahas mengenai sistem perbankan, baik bersifat konvensional maupun syariah. Konvesional menganut sistem bunga bank, sedangkan syariah menganut system bagi hasil. Temuan utama dari literatur menunjukkan bahwa bank syariah, melalui sistem bagi hasil, menawarkan distribusi kekayaan yang lebih adil dan dianggap memiliki mekanisme pembagian risiko yang lebih baik, terutama selama periode ketidakstabilan keuangan. Namun, sistem bagi hasil seringkali menghadapi tantangan terkait transparansi dan pemantauan, yang berpotensi mempengaruhi efisiensi operasional. Sebaliknya, bank konvensional, meskipun mendapatkan keuntungan dari struktur berbasis bunga yang lebih sederhana, dapat membuat nasabahnya terkena volatilitas suku bunga dan tidak memiliki dimensi keadilan sosial yang ditekankan dalam keuangan Islam].